1961
DOI: 10.1001/jama.1961.03040080036008
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Diabetes and Anorexigenics

Abstract: Previous observations on 62 obese diabetic patients showed that phenmetrazine hydrochloride significantly reduced appetite and weight. In the present study 30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1962
1962
1982
1982

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Some studies, however, have shown that phenmetrazine was much superior to either phendimetrazine or diethylpropion in producing weight loss. In these same studies, it was reported that phenmetrazine and phendimetrazine produced the same incidence of side effects, while diethylpropion produced fewer side effects (9,10).…”
mentioning
confidence: 89%
“…Some studies, however, have shown that phenmetrazine was much superior to either phendimetrazine or diethylpropion in producing weight loss. In these same studies, it was reported that phenmetrazine and phendimetrazine produced the same incidence of side effects, while diethylpropion produced fewer side effects (9,10).…”
mentioning
confidence: 89%
“…These were the inclusion of low‐caloric diets and particularly the psychologic impact of the physician‐investigator on the patient and the investigator's own conscious or unconscious bias. Gradually these undesirable features were reduced or neutralized by the evolution of more sophisticated, better‐controlled studies with double‐blind, cross‐over and total randomization factors (8–13). As the validity of the methodologies increased, the clinical evidence for the pharmacologic activity and hypo‐orexigenic quality of these drugs mounted.…”
Section: Early Scepticism—re‐evaluationmentioning
confidence: 99%
“…As the validity of the methodologies increased, the clinical evidence for the pharmacologic activity and hypo‐orexigenic quality of these drugs mounted. Eventually a method was derived which demonstrated an involuntary decrease in appetite in humans, with almost the same degree of objectivity as is attained in animal experiments (10, 13, 14). This was effected by the introduction of a very significant third blind factor.…”
Section: Early Scepticism—re‐evaluationmentioning
confidence: 99%
See 2 more Smart Citations